Faktor yang Berhubungan dengan Keberadaan Jentik Aedes aegypti di Daerah Endemis Demam Berdarah Dengue (DBD) Jakarta Barat - Heni Prasetyowati; Endang Puji Astuti; Mutiara Widawati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2017)
Dengue cases in the Capital City of Indonesia keep increasing year to year. West Jakarta accounted for 17.8% of total patients in Jakarta for the period 2012-2015. This is a cross-sectional design research, conducted in May 2015 in Kembangan, Grogol Petamburan and Cengkareng’s Health Centre, West Jakarta. This study aimed to analyse the relationship between the level of education, the use of anti-mosquito, and the presence of container in the community with the presence of Ae. aegypti larvae. Collection of data was conducted through interviews and surveys of larvae in 100 houses per health centres; the total samples were 300 households. The results showed that types of insecticide formulations widely used by respondents were spray and lotion. Most of the types of containers found in the survey area were buckets, tubs and jars/plastic barrel. Bivariate analysis using Chi-square showed that the educational level (p-value 0.045), layout (p-value 0.00), type (p-value 0.00) and the number of containers (p-value 0.00) have a significant relationship with the existence of larvae. There was no evidence of relation between the selection of formulation type (p-value 0,60) and the frequency of used household insecticide (p-value 0,30) in West Jakarta to the presence of Ae. aegypti larvae.